Could probiotics protect against human toxicity caused by polystyrene nanoplastics and microplastics? - Bazeli, Javad; Banikazemi, Zarrin; Hamblin, Michael R.; Sharafati Chaleshtori, Reza (Frontiers in Nutrition, 2023)
Nanoplastics (NPs) and microplastics (MPs) made of polystyrene (PS) can be toxic to humans, especially by ingestion of plastic particles. These substances are often introduced into the gastrointestinal tract, where they can cause several adverse effects, including disturbances in intestinal flora , mutagenicity, cytotoxicity, reproductive toxicity, neurotoxicity, and exacerbated oxidative stress. Although there are widespread reports of the protective effects of probiotics on the harm caused by chemical contaminants, limited information is available on how these organisms may protect against PS toxicity in either humans or animals. The protective effects of probiotics can be seen in organs, such as the gastrointestinal tract, reproductive tract, and even the brain. It has been shown that both MPs and NPs could induce microbial dysbiosis in the gut, nose and lungs, and probiotic bacteria could be considered for both prevention and treatment. . Furthermore, the improvement in gut dysbiosis and intestinal leakage after probiotics consumption may reduce inflammatory biomarkers and avoid unnecessary activation of the immune system.Herein, we show probiotics may overcome the toxicity of polystyrene nanoplastics and microplastics in humans, although some studies are required before any clinical recommendations can be made.